PERANCANGAN WEBSITE PADA PT. RATU ENIM PALEMBANG - Batubara, Febrin Aulia (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI TERAPAN "REINTEK" (REKAYASA INOVASI TEKNOLOGI), 2012)
Online shopping business start-known in Indonesia. Some advantages of online shopping is the marketing of products can reach consumers anywhere, the ease of both payment transactions and goods delivery, competitive pricing, product selection is varied, t he quality of the product can be communicated to consumers more transparent lagi.Tujuan of writing this thesis is to analyze and design website is also an online marketing system on PT. Ratu Enim Gallery so it could help market the products of fuel briquettes as a substitute for kerosene, LPG and charcoal is more efficient, safe, hot and easy to households and industry. The method used is the method of analysis and design methods. Analytical methods used to conduct surveys and questionnaires to PT. Ratu Eni m and consumers in order to get the proper analysis for the design of marketing systems at PT. Ratu Enim. Thus we can find out the advantages and disadvantages of this system. The results obtained from both methods is in the form of a website. Website PT. Ratu Enim serves as a means for the promotion of briquettes which provides various facilities, such facilities briquettes information about products and facilities to accommodate inquiries from consumers.